Vesicocervical Fistula Post Emergency Repeat Caesarean Delivery - Poudel, Rekha; Dangal, Ganesh; Karki, Aruna; Pradhan, Hema; Shrestha, Ranjana; Bhattachan, Kabin; Bajracharya, Nishma; Tiwari, Kenusha Devi (Nepal Journal of Obstetrics and Gynaecology, 2018)
Urogenital fistula is an abnormal communication between the urinary tract and genital tract at different levels, vesicocervical fistula being rare. It has been the consequence of poor obstetric care in developing world and iatrogenic following gynecologic surgeries in developed world. Diagnosis is mainly done by clinical examination, conventional dye test with methylene blue and imaging studies and cystoscopy, if required. Though prevention is better than cure, early detection followed by transurethral bladder drainage and surgical correction via vaginal or abdominal approach is the mainstay of treatment. A 30 years postnatal mother was referred to our centre with complaints of continuous involuntary leakage of urine per vaginum following emergency repeat caesarean delivery done six weeks back. There was pooling of urine over Sim’s speculum and dye test was positive. Under spinal anesthesia, vesicocervical fistula was repaired vaginally and patient was kept on Foley’s catheter for three weeks. Dye test performed at the end was negative. She went home dry and continent. We present here a rare case of successful repair of vesicocervial fistula post emergency repeat caesarean delivery.